Exacerbation of hypereosinophilic syndrome with pulmonary involvement in two consecutive pregnancies: a case report and review of the literature - Ghersin, Itai; Elias, Nizar; Slobodin, Gleb; Odeh, Majed (International Journal of Research in Medical Sciences, 2017)
Hypereosinophilic syndrome represents a heterogeneous group of disorders with the common feature of prolonged eosinophilia of unknown cause and organ system dysfunction including the pulmonary system. Hypereosinophilic syndrome, with and without pulmonary involvement, in association with pregnancy is very rare, and to the best of our knowledge only one case of hypereosinophilic syndrome with pulmonary involvement during pregnancy has been previously reported in the medical literature. We describe a case of a patient with previously symptomatic hypereosinophilic syndrome with pulmonary involvement who experienced exacerbations of her disease during two consecutive pregnancies. To the best of our knowledge this is the first report which demonstrates a worsening effect of pregnancy on both eosinophil count and end organ involvement in a patient with previous diagnosis of hypereosinophilic syndrome.